Material de enseñanza virtual para escritura creativa de cuentos de terror (2018)
While the pedagogical practice of the Spanish and English Language program carried out at the Guillermo León School, a serious problem was evidenced when carrying out a writing exercise, since the classic methods for the construction of stories have been working, among them the neutral structure that does not allow seeing beyond the contextual reality. For this reason students have taken a certain disinterest in writing, they feel overwhelmed by this type of task. For this, it is intended to design a virtual teaching material that allows students to practice writing according to their interests and at the same time to promote creativity to produce authentic texts within the literary genre of the story.